O santo é brasileiro: história, memória, fé e mediação no estudo de santo Antonio de Sant Anna Galvão - Souza, Bianca Gonçalves de (2009)
The present thesis proposes a reflection about saint Antonio de Sant Anna Galvão, the first Brazilian to be canonized a saint by the Catholic Church. Therefore, the objective was to study and analyze how he became a saint and how historical, cultural and social elements contributed to make him into a different person to the eyes of thousands of devotees in the country. Friar Galvão was born in Guaratinguetá, São Paulo state, in 1739 and died in São Paulo city on December 23rd, 1822. The house in which he was born and lived with his family in his hometown works as a museum and memorial, and the Luz Monastery in São Paulo city is also a place of memory when we think of this man. It is also the place where he was buried. The specific objectives, therefore, were based on getting to know better what Friar Galvão s memories are made of, and based on these memories how social subjects, patrimony and individuals collaborate to build a canonic process that made him into a saint for the Catholic Church. The paper is justified by the need to understand how a canonization process is built historically. As it crosses the sacred universe, it is a matter that concerns the social life. Brazilian reality is diverse in its religions and as such deserved a study of the theme as it concerns symbolic, material and historical practices of the life of the human being. The methodological aspects were first based on a bibliographic study about the spoken history, memory, the press, images, objects and collections, patrimony, mediation and religiousness. Secondly, the research sources were surveyed: newspaper and magazine articles, electronic sources, photographs, recorded interviews with devotees and individuals that helped turn him into a saint. Thirdly, photographic registries were made to better understand the reality that surrounded him and to analyze critically the places of memory and of the patrimony. The first chapter deals with how the press covered the events of canonization and beatification. The second one recreates the discussion about miracle-receivers who contributed directly with their experiences to turn him into a saint. The third chapter talks about the miracle-receivers, devotees who visit the memory places related to Friar Galvão after his canonization and tell their experiences of faith and miracle with their devotion saint. The fourth chapter analyzes critically the patrimony and the objects related to the memory of Antonio Galvão de França. The premises for this paper were that Friar Galvão did not become a saint only because it was ordered by the Pope, but for being an individual who produced memories, and these memories, together with other individuals, is what built the image of a sanctified man. The research moved on to understanding that turning Friar Galvão into a saint depended on a patrimony built to reinforce his sanctity fame and especially on an important participation of groups religious, family, devotees groups that were responsible to make him part of the catholic group of saints. It was concluded that the process which made him occupy catholic altars is a historical development which implied in analyzes of disputes and decisions, in the active participation of social subjects and individuals who were parts of a whole that wants to show to everybody Friar Galvão as a Brazilian saint and as someone who is dear to followers all over Brazil